KIAI DI PERSIMPANGAN JALAN ANTARA PESANTREN DAN POLITIK - Kosim, Mohammad Kosim (KARSA: Journal of Social and Islamic Culture)
Abstrac It is tha nature of kiai to lead a pesantren, due to the fact that they are known as religious figures, advisor, owner and establisher of peasntren. Nevertheless, the involvement of kiai as a practical politic activist even they hold the top position of several political parties, elites of executive and legislative are interesting phenomena. Pesantren and politic are two different things. Pesantren is recognized as the institution of tafaqquh fi al-dien that weighs on religious aspects construction (ukhrawi). The kiai choice to get involved in practical politic would become a new challenge. It needs new ability which is different from the ability of managing pesanttren. Thus it is able to raise new problem. Then back to khittah is a "proper" choice. Kata-kata kunci Kiai, pesantren, politik